2015
DOI: 10.11118/actaun201563030717
|View full text |Cite
|
Sign up to set email alerts
|

Study of Dam-break Due to Overtopping of Four Small Dams in the Czech Republic

Abstract: Dam-break due to overtopping is one of the most common types of embankment dam failures. During the floods in August 2002 in the Czech Republic, several small dams collapsed due to overtopping. In this paper, an analysis of the dam break process at the Luh, Velký Bělčický, Melín, and Metelský dams breached during the 2002 flood is presented. Comprehensive identification and analysis of the dam shape, properties of dam material and failure scenarios were carried out after the flood event to assemble data for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Breach mechanism is classified as following: hydraulic failure, geo-hydraulic failure and global static failure, [20]. Hydraulic failure generally consists on overtopping [21] and wave scour on the dike structure, while geo-hydraulic failure is due to the seepage process through the dike core or foundation, which leads into the erosion process associated with transportation of significant materials amount. Whereas concerning to the type of breach mechanisms, if two aforementioned types are induced mainly from pressure forces as ice, water, and wind waves, while the third type of breach mechanisms (i.e.…”
Section: Dike Breaching Mechanismsmentioning
confidence: 99%
“…Breach mechanism is classified as following: hydraulic failure, geo-hydraulic failure and global static failure, [20]. Hydraulic failure generally consists on overtopping [21] and wave scour on the dike structure, while geo-hydraulic failure is due to the seepage process through the dike core or foundation, which leads into the erosion process associated with transportation of significant materials amount. Whereas concerning to the type of breach mechanisms, if two aforementioned types are induced mainly from pressure forces as ice, water, and wind waves, while the third type of breach mechanisms (i.e.…”
Section: Dike Breaching Mechanismsmentioning
confidence: 99%
“…There is usually more than one cause of the total failure of a structure like this. In this simulated case the reasons are a flood wave with parameters higher than the design flood wave and with the return period of more than 100 years and also the defective construction of the dam itself [26], [27]. The HEC-RAS software offers two types of failure mode -overtopping or piping.…”
Section: Modeling Of Unusual Flood Situations At Detention Reservoirsmentioning
confidence: 99%
“…Unfortunately assumption of the full protection for this type of structure is almost impossible because there is always a risk, even if a very small one. It is associated with the occurrence of phenomena such as overflowing, internal erosion or sabotage [1].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the causes of dike failures can be divided into three groups: the loss of stability (shearing failure along the sliding surface or cracking due to settlement), erosion, damage caused by water and overflowing. The statistics published in [1] showed that occurrence of the overflow caused approximately 40% of all dike failures. A number of authors have studied the mechanism of dike failures due to overflowing [2,3,4,5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%